Sensitivity Analysis of Biodiesel Blends on Benzo[A]Pyrene and Main Emissions Using Moves: A Case Study in Temuco, Chile - Cubillos-Montecino, F; Diaz-Robles, L; Pino-Cortes, E (Elsevier, 2015)
Temuco is one of the most highly wood-smoke polluted cities in Chile; however, the diesel mobile sources are growing very fast in the past 10years and so far very few studies have been done. The main goal of this research was to develop a 2013 emission inventory of criteria pollutants and Benzo[a]pyrene (BaP) and to evaluate the use of six biodiesel blends of 0%, 1%, 4%, 8%, 12%, and 20% by volume of fuel in diesel motors from the vehicle fleet within the mentioned areas using the Motor Vehicle Emission Simulator (MOVES). Input parameters for the base year 2005 were estimated to implement and adapt the model in Chile, while results of NOx, PM10, PM2.5, NH3, CO2 equivalent and SO2 were compared with the Chilean Emission Inventory estimated by the model "Methodology for the Calculation of Vehicle Emissions." The 2013 emissions reduced with respect to 2005, in the majority of the contaminants analyzed, despite the 47% increase in the annual miles traveled. Using biodiesel blends, an emission reduction was estimated at up to 15% in particulate matter, BaP, and CO for the year 2013, as well as an increment of 2% in NOx emissions, attributed to low sulfur content (50ppm) in the diesel and the antiquity of the vehicle fleet. The results obtained gave evidence of the influence of the biodiesel use in the pollutant emissions to improve the Chilean air quality, as well as providing a strategy for this air quality management. © 2015 Elsevier B.V.